Komunikasi Tradisi Abdaâ€™u pada Prosesi HewanQurban Adat Tulehu Maluku - Sulaeman sulaeman; Retna Mahriani; Ali Nurdin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
Abdaâ€™u tradition is performed on the feast of Muslimsâ€™ Aidul Adha. This tradition is a form of struggle, the defense of the flag, seizure of the sacrificed animalsâ€™ blood by enforcing the ideological teachings of Islam. The purpose of this research was to understand and find communication events, communication components, and patterns of abdaâ€™u communication tradition on Maluku Tulehu to sacrifice animalsâ€™ procession. This research uses the theory of symbolic interactionism of the constructivist paradigm and communication ethnography method "speaking" from Dell Hymes as the basic reference. The approach used is qualitative data collection techniques through in-depth interviews, participant observations, the study of librarianship and documentation. The subject of the study amounted to 13 people and 2 key informants whom the abda'u offender, directory and mosque imam through a purposive sampling technique. The results of the abdaâ€™u tradition communication events include purified sacrifice animals, upholding the religion flag, and the sacrifice of animal slaughtering. Communication events occur concerning the house on mosque Imam, the villages, and Jami'i mosques. The message conveyed in Tulehu religious language, either verbal or nonverbal, based on the lofty norms and values passed down from generation to the next generation. The communication pattern formed based on abda'u tradition of awareness to preserve the procession of sacrificed animals through devotion to God Almighty by enforcing Islam ideological, syiar of Islam, the sacrifice of the sacrificed animals to the community, and the social solidarity of Muslim community. Tradisi abdaâ€™u dilakukan pada hari perayaan Idul Adha umat Islam. Tradisi ini merupakan bentuk perjuangan, pertahanan dan penegakkan bendera serta perebutan darah hewan qurban dengan menegakkan ideologi ajaran Islam. Tujuan penelitian ini untuk memahami dan menemukan peristiwa komunikasi, komponen komunikasi, dan pola komunikasi tradisi abdaâ€™u pada prosesi hewan qurban adat Tulehu Maluku. Penelitian ini menggunakan teori interaksionisme simbolik dari Blummer dengan paradigma konstruktivis dan metode etnografi komunikasi â€œspeakingâ€ dari Dell Hymes sebagai acuan dasarnya. Pendekatan yang digunakan dalam penelitian adalah kualitatif dengan teknik pengumpulan data melalui pengamatan partisipan, wawancara mendalam, studi kepustakaan, dan dokumentasi. Subjek penelitian berjumlah 13 orang dan 2 orang narasumber kunci melalui teknik purposive sampling. Hasil penelitian menunjukkan bahwa peristiwa komunikasi tradisi abdaâ€™u meliputi hewan qurban disucikan, perebutan bendera religi, dan penyembelihan hewan qurban. Peristiwa komunikasi terjadi di kediaman rumah Imam masjid, jalan kampong, dan masjid Jamiâ€™i. Pesan disampaikan bernada religi menggunakan bahasa Tulehu, baik verbal maupun nonverbal berlandaskan kepada norma dan nilai luhur diwariskan dari generasi kepada generasi berikutnya. Pola komunikasi tradisi abdaâ€™u dibentuk atas dasar kesadaran untuk melestarikan prosesi hewan qurban melalui pengabdian kepada Allah SWT dengan menegakkan ideologi ajaran Islam, syiar Islam, pengorbanan hewan qurban untuk masyarakat, dan solidaritas sosial sesama komunitas Muslim.